Vacancy Formation and Clustering Behavior in δ-MoN: A Systematic Density Functional Theory Study - Jing Yu; Keda Wang (Nanomaterials)
Molybdenum nitrides are known to have a series of excellent physical properties owing to their unique bonding nature and electronic structure. However, the synthesized samples often exist in nonstoichiometric phases with structural defects (metal or non-metal vacancies), which may influence their performance. Based on the density functional theory, we theoretically studied the vacancy formation in δ-MoN. Various configurations that contained one single vacancy, divacancies, or trivacancies were constructed and systematically studied. It was found that Mo vacancy leads to significant electron loss at the vacant site while N vacancy results in excess electrons being trapped, forming a uniform electron gas region. Detailed analysis revealed that four types of binding clusters are encouraged to form in δ-MoN. The VMo–VN or VN–VMo–VN (with a sandwich structure) binding is owing to the positive and negative interaction between Mo and N vacancies. The VN–VN or VN–VN–VN binding is attributed to the overlap of electron density, but requires N vacancies to be distributed in a specific arrangement. Both Mo and N vacancies induce the anisotropic degradation of electronic conductivity in δ-MoN, with the extent of degradation governed by the vacancy type and concentration.